Web-Based Accounting Information System for a Building Materials Trading Company Case Study on CV. Cahaya Terang Metalindo - Levina Cahyono; FX. Hendra Prasetya; Agnes Advensia Chrismastuti (Soegijapranata Catholic University, 2026)
Global competition drives businesses to innovate and leverage technology. This research focuses on CV. Cahaya Terang Metalindo, which still uses a manual system in its operations. The accounting information system developed using the RAD method aims to record sales transactions, purchases, cash disbursements, and generate financial reports. This web-based system is developed with the PHP programming language and the Laravel framework, and applies the FIFO inventory valuation method. After using this system, the owner acknowledges an increase in business effectiveness and efficiency, as well as the accuracy of financial reports.